Analysis of Surface Properties in Drilling of Different Die Steels used in Manufacturing Industries - Vipin (My University, 2012)
The objective of the work is to analysis of surface properties in drilling of different die steels used in manufacturing industries. A study of the machining sector showed the drilling process is one of the most important due to both number of operations and machine time consumed. The importance of this process is even higher in aerospace industry, heat exchanger, die making and in aircraft manufacturing. As surface roughness is the main problem in drilling of various materials. This is due to various process parameters whether it is due to controllable or uncontrollable factors. The surface roughness will result in about 30% of parts reduction. The roughness will measure from surface roughness tester and average value of surface roughness will find out. The design of experiment approach has been applied for designing the experimentation work. The optimization of process parameters has been done by analysing the results.
M.E. (Production and Industrial Engineering)
Keywords: Drilling; Surface Properties